Comparative Transcriptomics and Proteomics Analyses of Leaves Reveals a Freezing Stress-Responsive Molecular Network in Winter Rapeseed (Brassica rapa L.) - Wei, Jiaping; Zheng, Guoqiang; Yu, Xingwang; Liu, Sushuang; Dong, Xiaoyun; Cao, Xiaodong; Fang, Xinling; Li, Hui; Jin, Jiaojiao; Mi, Wenbo; Liu, Zigang (Frontiers in Plant Science, 2021)
Winter rapeseed is susceptible to low temperature during winter in Northwest China, which could lead to severe reduction of crops production. The freezing temperature could stress the whole plant, especially on leaf, and ultimately harm the survival rate of winter rapeseed. However, the molecular mechanism underlying freezing tolerance is still unclear in winter rapeseed. In this study, a comprehensive investigation of winter rapeseed freezing tolerance was conducted at the levels of transcript, protein, and physiology and biochemistry, using a pair of freezing-sensitive and freezing-resistant cultivars NQF24 and 17NTS57. There were 4319 unique differentially expressed genes (DEGs) and 137 unique differentially abundant proteins (DAPs) between two cultivars identified in leaf under freezing stress. Function enrichment analysis showed that most of enriched DEGs and DAPs were involved in plant hormones signal transduction, alpha-linolenic/linoleic acid metabolism, peroxisome, glutathione metabolism, fatty acid degradation, and secondary metabolites biosynthesis pathways. Based on our findings, it was speculated that freezing tolerance formation is caused by increased signals transduction, enhanced biosynthesis of protein, secondary metabolites and plant hormones, elevated energy supply, greater reactive oxygen species scavenging and lower lipid peroxidation, as well as stronger cell stability in leaf under freezing stress. These results provide comprehensive profile of leaf response under freezing stress, which have potential to be used as selection indicators breeding program to improve freezing tolerance in rapeseed.